Kajian Literatur: Dampak Aktivitas Penambangan Terhadap Biodiversitas dan Lingkungan - Putri, Nadiah Danisha; Devia Selviana; Erna Heryanti; Diana Vivanti Sigit (Health Safety Environment, 2025)
Background : The ongoing mining activities in various regions of Indonesia have raised concerns about environmental sustainability and biodiversity conservation. The unsustainable management of natural resources, particularly in the form of open-pit mining and the use of hazardous chemicals, has caused significant ecological damage, such as deforestation, water and air pollution, and the loss of wildlife habitats. This study aims to systematically assess the impact of mining activities on biodiversity and the environment. Methods : This study uses a literature review method. Data were obtained through a search of scientific articles published between 2020 and 2025 on Google Scholar, focusing on Indonesia. The search using keywords such as impact, mining, environment, and biodiversity resulted in 2,600 articles. From these, ten articles were selected based on inclusion criteria: scientific articles in Indonesian, available full-text, focusing on Indonesia, discussing the impacts of mining on the environment and/or biodiversity, and aligning with the set keywords. The analysis was conducted descriptively with a thematic approach Result : The study results show that mining activities have a negative impact on ecological conditions, both on land and in aquatic environments, and exacerbate environmental damage due to weak supervision and low compliance with environmental regulations. Conclusion : In conclusion, mining activities in Indonesia generally do not prioritize sustainability principles. Strengthening regulations, supervision, and management focused on long-term conservation and environmental protection is necessary